The Young Carers’ Journey: A Systematic Review and Meta Ethnography - Saragosa, Marianne; Frew, Melissa; Hahn-Goldberg, Shoshana; Orchanian-Cheff, Ani; Abrams, Howard; Okrainec, Karen (International journal of environmental research and public health, 2022)
Despite growing international interest, the caregiving body of literature lacks a recent understanding of young carers’ experiences and their contact with the health care system. We conducted a systematic review of qualitative studies to (1) synthesize more recent qualitative evidence on young carers’ experience, and (2) to identify how these young carers interact with the health care system in their caregiving role. Using a meta-ethnographic synthesis, a total of 28 empirical studies met inclusion. Key findings helped inform an overarching framework of the experience of young carers as illustrated by a journey map. The journey map is a visual depiction of the stages these young carers go through when in a caregiving role framed by three themes: (1) encountering caregiving; (2) being a young caregiver, and (3) moving beyond caregiving. The caregiving experience is perceived by young people as challenging and complex, which could be improved with more informational navigation and emotional support. Understanding these experiences provides insight into gaps in health services and potential solutions that align with the stages outlined in the journey map.